A retrospective observational study on the prognostic role of inflammatory markers in futile recanalization after endovascular treatment for large-vessel stroke - Zubing Xu; Linghong Guo; Yunqing Chen; Dandan Chen; Hudie Zhang; Xilin Xiong; Yan Gong; Qiulong Yu; Chenying Zeng; Lanjiao Zhang; Qin Huang; Jinchong Zhang; et al. (Journal of International Medical Research)
Objective Endovascular treatment has proven to be effective in improving the outcome of patients with large-vessel stroke. However, more than half of the patients experience poor outcomes despite successful recanalization, which was defined as futile recanalization. The present study aimed to identify the relationship between multiple inflammatory markers (before and after endovascular treatment) and futile recanalization. Methods Between November 2019 and September 2022, we retrospectively enrolled 456 patients according to the inclusion and exclusion criteria. Inflammatory variables, including neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, systemic immune-inflammation index, systemic inflammatory response index, systemic coagulation-inflammation index, and white blood cell count to mean platelet volume ratio, were collected. Results Among the cohort of 456 patients, it was observed that 271 (59.4%) patients experienced futile recanalization. Univariate analysis revealed that patients with futile recanalization had higher neutrophil-to-lymphocyte ratio and systemic inflammatory response index but lower lymphocyte-to-monocyte ratio and systemic coagulation-inflammation index at admission compared with those without (p < 0.05). Additionally, at postoperation, patients with futile recanalization had higher neutrophil-to-lymphocyte ratio, systemic inflammatory response index, and systemic immune-inflammation index but lower lymphocyte-to-monocyte ratio and systemic coagulation-inflammation index compared with those without (p < 0.05). However, there were no significant differences in admission platelet-to-lymphocyte ratio, admission systemic immune-inflammation index, admission white blood cell count to mean platelet volume ratio, postoperation platelet-to-lymphocyte ratio, and postoperation white blood cell count to mean platelet volume ratio between the futile recanalization group and nonfutile recanalization group (p > 0.05). Furthermore, multivariate logistic regression analysis showed that only admission systemic inflammatory response index, postoperation neutrophil-to-lymphocyte ratio, postoperation systemic inflammatory response index, and postoperation systemic immune-inflammation index remained significantly correlated with futile recanalization (p < 0.05). Receiver operating characteristic curves revealed that postoperation neutrophil-to-lymphocyte ratio was the most predictive marker for futile recanalization (area under the curve = 0.623, 95% confidence interval: 0.572–0.675). Conclusion Admission systemic inflammatory response index, postoperation neutrophil-to-lymphocyte ratio, postoperation systemic inflammatory response index, and postoperation systemic immune-inflammation index were independently associated with futile recanalization, and postoperation neutrophil-to-lymphocyte ratio may have the highest ability in predicting futile recanalization in patients who underwent endovascular treatment.